A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India - Ng, Heok Hee; Lalramliana, Lalramliana; Lalronunga, Samuel (Zootaxa, 2016)
This study describes a new diminutive sisorid catfish from the upper reaches of the Karnaphuli River drainage in northeastern India. The new species can be distinguished from congeners in having a combination of: length of dorsal-fin spine 18.0–21.6% SL; 4–10 serrations on the anterior edge of the dorsal spine; length of pectoral-fin spine 20.7–26.1% SL; length of adipose-fin base 21.5–26.3% SL; body depth at anus 12.3–15.9% SL; caudal peduncle depth 7.5–9.8% SL; caudal peduncle length 17.0–20.5% SL; pale, y-shaped marking on dorsal surface of head; sides of body with pale yellowish patches and irregular bands.